Chemical and Hydro-chemical Studies of Ground Water Quality for Irrigation near the Treated Sewage Water Tanks in Eastern Dry Zone of Karnataka - , H. N. NAYANA, D. V. NAVEEN, RUDRAGOUDA CHILUR, S. DAYANANDANAIK, AISHWARYA, V, V. VENKATACHALAPATHI (Archives of Current Research International, 2025)
Groundwater is a main source Eastern Dry Zone of Karnataka where it is used for domestic, irrigation and industrial purposes. The recharge of ground water last five years by treated sewage water which is discharge form Bangalore metropolitan city and this water is mainly used for irrigation. The main objective of this study was to assess the chemical and hydro-chemical properties of groundwater and to determine its suitability for irrigation in this zone. Using GPS tool 50 groundwater samples were collected. These samples analysed for various parameters like pH, EC, Sodium Adsorption ratio (SAR), Residual sodium carbonate (RSC), Total dissolved salts (TDS) and Total hardness (TH), cations (Ca2+, Mg2+, Na+, K+) and anions (HCO3-, CO3-, SO4-, Cl-, NO3-, F-, PO42-). Results indictes that groundwater is neutral to slightly alkaline with pH values between 7.1 and 8.2. Total soluble salts (electrical conductivity) 587 μmhos cm-1, Sodium Adsorption Ratio 0.54, Residual sodium carbonate -5.37 meq L-1, TDS (382.69 mg L-1) was found to be normal and total hardness (596.16 mg L- 1) is more. From the piper trilinear diagram, water quality belongs to calcium-magnesium- chloride-sulphate type. All cations and anions are in suitable range for irrigation purpose except chloride (11.06 meq L-1) and fluoride (3.06 mg L-1). According to the US salinity classification, the majority of samples were acceptable for irrigation.